Age-related ceRNA networks in adult Drosophila ageing - Yang, Deying; Xiao, Feng; Li, Jiamei; Wang, Siqi; Fan, Xiaolan; Ni, Qingyong; Li, Yan; Zhang, Mingwang; Yan, Taiming; Yang, Mingyao; He, Zhi (Frontiers in Genetics, 2023)
As Drosophila is an extensively used genetic model system, understanding of its regulatory networks has great significance in revealing the genetic mechanisms of ageing and human diseases. Competing endogenous RNA (ceRNA)-mediated regulation is an important mechanism by which circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs) regulate ageing and age-related diseases. However, extensive analyses of the multiomics (circRNA/miRNA/mRNA and lncRNA/miRNA/mRNA) characteristics of adult Drosophila during ageing have not been reported. Here, differentially expressed circRNAs and microRNAs (miRNAs) between 7 and 42-day-old flies were screened and identified. Then, the differentially expressed mRNAs, circRNAs, miRNAs, and lncRNAs between the 7- and 42-day old flies were analysed to identify age-related circRNA/miRNA/mRNA and lncRNA/miRNA/mRNA networks in ageing Drosophila. Several key ceRNA networks were identified, such as the dme_circ_0009500/dme_miR-289-5p/CG31064, dme_circ_0009500/dme_miR-289-5p/frizzled, dme_circ_0009500/dme_miR-985-3p/Abl, and XLOC_027736/dme_miR-985-3p/Abl XLOC_189909/dme_miR-985-3p/Abl networks. Furthermore, real-time quantitative PCR (qPCR) was used to verify the expression level of those genes. Those results suggest that the discovery of these ceRNA networks in ageing adult Drosophila provide new information for research on human ageing and age-related diseases.